Kekasaran Permukaan Fiber Reinforced Composite Setelah Perendaman Dalam Asam Sitrat Minuman Energi - Rara Anjani Kusuma Dewi, - (2017)
Background: The surface roughness of restoration is initiated by a degradation process which may be caused by acidic food and beverage consumption. Fiber Reinforced Composite is a composite which is consist of micron fiber filler, with good mechanical properties. Energy drink is a drink which can improve physical performance and body endurance an its demand have been increased by 56% in the last two decades, especially in teenagers and young adults. This drink contains a large amount of citric acid and is erosive for dental and restoration. Purpose: To find out about the surface roughness of Fiber Reinforced Composite after immersion in energy drink's citric acid Methods: The energy drink X was analyzed using HP LC to test the concentration of citric acid which is contained in the drink. 32 disc shaped samples with the size of 5mm in diameter and 2mm in height of FRC were prepared Before and after the immersion, the surface roughness of the samples were tested using Surface Roughness Tester, Mitutoyo SJ-201. After that, all the 32 samples were immersed in Aquadest inside an incubator with 37°C temperature. They were divided in two groups with 16 samples in each group. In group 1, the samples were immersed in 3364,81ppm of citric acid solution which corresponds the result of the previous HP LC test. In group 2, the samples were immersed in aquadest as the control. Both groups are immersed for 2 4 hours in incubator with 37°C of temperature. Then, all of the surface roughness of the samples were tested by using the same instrument as the before immersion test. Results: Data were analyzed by Independent T-Test with the result of p=O,OOO(p<0,05). It shows that there is a significant difference between 2 groups. Conclusion: After immersion in 3364,81ppm citric acid, the surface roughness of Fiber Reinforced Composite Resin is increased